Stationary quasivariational inequalities with gradient constraint and nonhomogeneous boundary conditions - Azevedo, Assis (2014)
Publicado em "From particle systems to partial differential equations. Part 2. (Springer proceedings in mathematics & statistics, vol. 75). ISBN 978-3-642-54270-1